2005
DOI: 10.1111/j.1532-5415.2005.53153.x
|View full text |Cite
|
Sign up to set email alerts
|

Homocysteine and Cognitive Function in a Population‐Based Study of Older Adults

Abstract: Higher homocysteine levels were associated with worse function across a broad range of cognitive domains, and the magnitude of the associations was large. The data suggest that homocysteine may be a potentially important modifiable cause of cognitive dysfunction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
81
0
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 110 publications
(88 citation statements)
references
References 36 publications
6
81
0
1
Order By: Relevance
“…The APOE ε4 cohort (2/4, 3/4, 4/4) represented 25.8% of our sample. This representation is within the range (24-30%) reported in other studies of APOE [16,29,30]. Mean cognitive scores for non-diabetic and diabetic individuals with adjustment for variables in the basic and basic+RF+CVD models are shown in Table 3.…”
Section: Resultssupporting
confidence: 75%
“…The APOE ε4 cohort (2/4, 3/4, 4/4) represented 25.8% of our sample. This representation is within the range (24-30%) reported in other studies of APOE [16,29,30]. Mean cognitive scores for non-diabetic and diabetic individuals with adjustment for variables in the basic and basic+RF+CVD models are shown in Table 3.…”
Section: Resultssupporting
confidence: 75%
“…Homocysteine has been linked to mild cognitive impairment and other aspects of cognitive decline [36,41]. Initially, high plasma total homocysteine was linked to atherothrombotic disease [42].…”
Section: Homocysteinementioning
confidence: 99%
“…Other studies have demonstrated that high plasma levels of homocysteine are associated with poorer neurobehavioral test performance in the elderly; subjects with HyHcy perform worst in all cognitive domains but were strongest in the domains related to simple motor and psychomotor speed and eye-hand coordination [25]; on the other hand, controversial results have been obtained on a possible reduction in spatial learning and other cognitive tasks in rats with diet-induced HyHcy [26,27].…”
Section: Discussionmentioning
confidence: 87%